Endovascular Treatment Combined With Standard Medical Treatment Improves Outcomes of Posterior Circulation Stroke: A Systematic Review and Meta-Analysis - Dong, Shuju; Li, Yanbo; Guo, Jian; Luo, Yaxi; Fang, Jinghuan; Tang, Li; He, Li (Frontiers in Neurology, 2022)
Aims Whether endovascular treatment (EVT) can further improve the prognosis of patients with posterior circulation ischemic stroke (PCIS) is unclear. This meta-analysis aims to compare the efficacy and safety of PCIS patients treated with EVT plus standard medical treatment (SMT) and SMT alone. Methods We systematically searched for relevant randomized controlled trials (RCTs) and prospective cohort trials in MEDLINE, EMBASE, and the Cochrane Library up to February 2022. The primary outcome was favorable functional outcome of the modified Rankin Scale (mRS) with scores of 0–2 or 0–3; secondary outcomes included successful recanalization rate, intracranial hemorrhage (ICH), or symptomatic intracranial hemorrhage (sICH) after treatment and 90-day mortality. Results We identified six studies including 1, 385 PCIS patients (957 with EVT plus SMT; 428 with SMT alone). EVT plus SMT substantially improved 90-day functional outcomes compared with SMT alone [mRS score of 0–2: RR=1.95, 95% CI (1.52 – 2.51), P < 0.001; mRS score of 0–3: RR = 1.85, 95% CI (1.49 – 2.30), P < 0.001, respectively]. Moreover, compared with SMT, combined treatment significantly improved the rate of successful recanalization [RR = 5.03, 95% CI (3.96–6.40), P < 0.001] and reduced 90-day mortality [RR = 0.71, 95% CI (0.63–0.79), P < 0.001] despite a higher risk of ICH [RR = 6.13, 95% CI (2.50–15.02), P < 0.001] and sICH [RR = 10.47, 95% CI [2.79–39.32), P = 0.001]. Conclusion Low-to-moderate evidence from RCTs and non-RCTs showed that increased ICH and sICH risk of EVT plus SMT did not translate to a higher risk of unfavorable outcomes compared with SMT and could even promote independence at 90 days in a real-world cohort.